IMPLEMENTASI PENGEMBANGAN PARIWISATA DI PANTAI KELAPA KELURAHAN PANYURAN KECAMATAN PALANG KABUPATEN TUBAN - Kusno Nugroho (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2018)
Coconut Panyuran Beach which is located in Tuban Regency, East Java Province, which is meant on the border of Palang and Tuban Subdistricts, is one of the most famous beach tourism attractions and is visited by many tourists. Based on the potential and opportunities that exist, the development of tourism needs to be done in order to increase economic growth by empowering the people's economy. researchers are interested in knowing how the implementation of tourism development in Tuban Regency, and knowing the right model in developing the tourism potential of Pantai Kelapa in improving the welfare of the surrounding community. This research is a qualitative descriptive study, with research objects in Panyuran and POKDARWIS villages using triangulation techniques.The results of this study are 1. Implementation of Regional Regulation number 9 of 2012 concerning Tuban District Spatial Plan for 2012-2032 based on Edware III theory consisting of (1) communication, (2) resources, (3) disposition, and (4) bureaucratic structure.Suggestions, socialization and good host training must be immediately scheduled and carried out to the community around the tourist attractions so that the community is always friendly towards visitors and the Standard Operating Procedure (SOP) needs to be formulated immediately.